Theoretical analysis of grouting reinforcement for surrounding rock of deep shaft based on stability and water inflow control - Xiang, Peng; Ji, Hong Guang; Zhang, Guang Quan; Li, Wen Guang (Frontiers in Earth Science, 2023)
Aiming at the problem of grouting reinforcement of deep shaft to control water, the elastic-plastic analytical formula for grouting surrounding rock under the combined action of thermal, hydraulic and mechanical fields is established based on Mohr-Coulomb yield criterion, and the variation rules and influencing factors of stability and impermeability of the grouting surrounding rock are calculated and analyzed. The analysis shows that the damage of surrounding rock is aggravated by the action of deep high ground temperature and high water pressure, and the influence of water pressure is particularly significant. The larger the radius and cohesion of the grouting surrounding rock, the smaller the radius of its plastic zone. With the increase of elastic modulus ratio between the grouting surrounding rock and the original rock, the radius of its plastic zone increases, so the elastic modulus of the grouting surrounding rock design should consider the original surrounding rock. With the decrease of permeability coefficient of grouting surrounding rock, the radial stress decreases, the tangential stress increases, and the radius of the plastic zone increases, the development of plastic zone not only affects the stability, but also causes the increase of permeability coefficient. There is mutual restriction and influence between the shaft water inflow, the permeability coefficient, the radius of grouting surrounding rock and the radius of its plastic zone. In the design of grouting reinforcement, the stability of surrounding rock and the control requirements of shaft water inflow should be considered comprehensively, and the optimal parameters should be selected based on theoretical calculation. The study can provide a theoretical basis for the optimization of grouting reinforcement parameters in deep shaft.